Knowledge, attitude and practice of infection control methods among health care workers - Devaliya, Jaydeep J.; Damor, Raman D.; Chawada, Bansari L. (International Journal Of Community Medicine And Public Health, 2017)
Background: Disposal of biomedical waste is neglected issue even in the urban heath care settings. So chances of transmission of infection increase which leads to high morbidity and mortality. Spread of disease can also be controlled by establishing isolation ward and it can be monitored through Hospital Infection Control Committee. Methods: This is a cross sectional study conducted in urban and rural health care settings of Ahmedabad district to assess the knowledge, attitude and practice of health care workers. In the present study 300 HCWs including Doctors, Nurses, Technicians and Servants were interviewed. Pre-tested questionnaire was used to collect the data regarding knowledge of infection control methods and various waste disposal practices. Results: Only 51% of health care workers were aware about the Isolation ward and 60% of HCWs were aware about hospital infection control committee. 87% nurses were correctly disposing gloves in urban health care settings. All the HCWs were using disposable syringe. Even in urban settings also 33% of doctors and 20% of nurses were recapping needle after using it. Conclusions: Constant reinforcement of knowledge should be done and regular training should be given to change the behavior regarding biomedical waste disposal.